A Historical Account of Wildlife Protection and Management in Tamil Nadu - Sekar, T. (Indian Forester, 2011)
India is endowed with rich biodiversity and a vast array of natural landscapes. The State of Tamil Nadu has also got varied forest types and is characterized by diverse flora and associated fauna. Wildlife protection in the Madras Presidency received some attention by way of promulgation of few laws and declaration of certain areas as sanctuaries in the early period of forest administration prior to independence. More Protected Areas were established in the post-independence decades. With the enactment of Wildlife Protection Act 1972, species-specific conservation programmes gained momentum. Between then and the close of 20th century, many more sanctuaries and national parks were constituted. The new millennium witnessed addition of more areas to protected area network and introduction of landscape-based approach for wildlife conservation, particularly for elephants and tigers. The State has at present 4,578 km2 of forests, accounting for 20% of the total extent of forest area brought under PA management. The unique biodiversity significance of these areas, conservation measures taken and their results in improving the population status of many flagship species have been discussed.